Jonathan Dean
XXI, 225 p. 32 illus., 16 illus. in color.
Keywords: Jonathan Dean (1924-2014) was a distinguished U.S. diplomat (1950-1980) and from 1984 to 2007 global security adviser to the Union of Concerned Scientists, Washington, D.C. During the 1980s and 1990s he was a pioneering conceptual thinker, writer and speaker on détente in Europe, global cooperative security, arms control and disarmament. He authored: Watershed in Europe (1987), Meeting Gorbachev’s Challenge (1989) and Ending Europe’s Wars (1994). This volume contains his biography and bibliography, six texts on détente and arms control in Europe in the 1980s: Beyond First Use; MBFR; Alternative Defence; Berlin; A Crisis Management Center; Conventional Arms Control in Europe and six texts on the new security order in Europe since the 1990s: Components of a Post-Cold War Security System for Europe; Constraining Technological Weapons Innovation; NATO Enlargement: Act II; Ten Years after the Wall; Future Security in Space; Rethinking Security: Return to the Grotean Pattern.